Analisis Statistik Distribusi Kejadian Gempabumi Di Luwu Timur, Morowali, Dan Morowali Utara, Sulawesi - Imanuela Indah Pertiwi (Jurnal Geofisika, 2022)
The tectonic conditions of East Luwu, Morowali and North Morowali, which are very complex, are traversed by main and local faults, making it possible to cause large earthquakes with a strength of M≥5. This research was conducted with the aim of knowing the distribution statistics of earthquakes in East Luwu, Morowali and North Morowali. The research area was selected at 1,00oS – 3,50oS dan 120,50oE– 122,50oE. The data used is the earthquake parameter data from IRIS-DMC (Incorporated Research Institutions for Seismology Data Management Centre) earthquake catalog from 1961 to 2020. The Poisson distribution method used in the analysis of the distribution of large earthquakes, produces a graph which shows that the actual Pr% value is above the theoretical Pr% Poisson, which means that the occurrence of large earthquakes (M≥5) in the East Luwu, Morowali and North Morowali areas did not occur in the ungroups type. The spatial distribution of the b-value shows a high value in the East Luwu and Morowali areas compared to the North Morowali area. Statistically, the value of the seismicity index and the probability of an earthquake event in East Luwu, Morowali, and North Morowali decrease as the magnitude of the earthquake increases. It is inversely proportional to the rapid recurrence time in earthquakes with a magnitude M≥5 and a long recurrence time at a greater magnitude.